PERAMPANEL IN THE TREATMENT OF REFRACTORY EPILEPSY IN EVERYDAY CLINICAL PRACTICE IN ADOLESCENTS - S. G. Burd; M. B. Mironov; M. M. Gunchenko; M. N. Sarzhina (Эпилепсия и пароксизмальные состояния)
The article presents modern data on the use of perampanel in antiepileptic drug therapy resistant epilepsy in routine clinical practice in adolescents. Despite the well-developed diagnostics and treatment of epilepsy system, about onethird of patients with newly diagnosed disease is resistent to medical therapy. When you select a combination of AEDs for children and adolescents should be borne in mind that school performance can largely predetermine their future. In this regard, the most feared cause such adverse events (AEs) as cognitive, neuropsychological, psychiatric and behavioral disorders. In the review perampanel demonstrates efficacy and safety, including among adolescents. There were shown the prospects of the usage of perampanel as add-on therapy of focal seizures with or without secondary generalization and a clinical case of application perampanel a patient with refractory epilepsy in adolescence.